2017
DOI: 10.1002/nau.23264
|View full text |Cite
|
Sign up to set email alerts
|

The role of male slings in post prostatectomy incontinence: ICI‐RS 2015

Abstract: It is important to understand how male slings work and by doing so we are more reliably able to choose the appropriate sling, predict outcomes, and as a result counsel patients. Suggestions for future research are proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…That could sustain an opinion that ATOMS may be an optimal choice in irradiated patients, also for diminished risk of complications such as urethral atrophy or erosion [15]. However, a recent series with predominance of SSP confirmed that both radiation and SUI severity are independent risk factors for ATOMS failure [12], but these risk factors also determine worse results both for retrobulbar male slings [5, 32] and for AUS [6, 33]. The use of the latest generation device with SSP also reveals better dry rates than reports with devices of predominantly previous generations, but contrary to previous belief [12], not a significant lower risk for complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…That could sustain an opinion that ATOMS may be an optimal choice in irradiated patients, also for diminished risk of complications such as urethral atrophy or erosion [15]. However, a recent series with predominance of SSP confirmed that both radiation and SUI severity are independent risk factors for ATOMS failure [12], but these risk factors also determine worse results both for retrobulbar male slings [5, 32] and for AUS [6, 33]. The use of the latest generation device with SSP also reveals better dry rates than reports with devices of predominantly previous generations, but contrary to previous belief [12], not a significant lower risk for complications.…”
Section: Discussionmentioning
confidence: 99%
“…Further development of adjustable slings with the possibility of postoperative adjustment has widened the spectrum of SUI severity that can be treated with the transobturator perineal approach. Different devices are now available to allow a personalised surgical approach for male SUI [1, 57].…”
Section: Introductionmentioning
confidence: 99%
“…Seventy-eight patients (88.6%) that underwent AUS implantation received postoperative antibiotics for a median of 8 days (1-25), and 53 patients (40.2%) that underwent implantation of an adjustable sling received postoperative antibiotics for a median of 5 days (1-20). The median postoperative time until catheter removal was 3 days [2][3][4][5][6][7][8][9][10][11][12][13][14][15] for patients receiving an AUS and 2 days [1][2][3][4][5][6][7][8][9][10][11] for patients receiving an adjustable sling.…”
Section: Resultsmentioning
confidence: 99%
“…Preoperative patient selection seems to be crucial for a satisfying postoperative result, but guideline recommendations are limited and mainly based on the severity of the incontinence [5]. A current review by Sahai et al [13] evaluating the role of male slings in postprostatectomy incontinence concluded that future research should focus on studies comparing sling systems and the AUS with an evaluation of patient factors such as etiology, severity, or prior surgery. Because of the less-invasive surgical approach without a need to manually operate the device, patients who are given the choice tend to choose a male sling system [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation